A Goal-Directed Model of Collaborative Decision Making in Hospice and Palliative Care. Issue 2 (April 2022) - Washington, Karla T.; Demiris, George; White, Patrick; Mathis, Holly C.; Forsythe, John E.; Parker Oliver, Debra
Hospice and palliative care teams face numerous barriers to the meaningful involvement of patients and families in medical decision making, which limits opportunities for exploration of the very values, preferences, and goals that ideally inform serious illness care. Researchers who develop and test interventions to address these barriers have noted the complementary utility of two existing models in supporting collaborative relationships between hospice and palliative care teams and the patients and families they serve: (1) the social problem-solving model, and (2) the integrative model of shared decision making in medical encounters. This paper describes the integration and extension of these two highly synergistic models, resulting in a goal-directed model of collaborative decision making in hospice and palliative care. Directions for practice innovation and research informed by the model are discussed at length.